Burnout Syndrome and Associated Factors in Intensive Care Unit Nurses - Aragão,Núbia Samara Caribé de (2021)
ABSTRACT Objective: to estimate prevalence and factors associated with Burnout Syndrome in intensive care nurses in a city in the state of Bahia. Methods: a cross-sectional, population-based study carried out with 65 intensive care nurses through a self-administered questionnaire, from July to November 2016, containing sociodemographic data, lifestyle, work characteristics. To define burnout syndrome, the Maslach Burnout Inventory was used. Results: Burnout Syndrome prevalence was 53.6%, an association was observed with age, tobacco consumption, alcohol use, weekly night shift hours, employment relationship, having an intensive care specialist title, number of patients on duty, monthly income and considering active or high-strain job. Conclusion: the results of this study can contribute to expanding the discussion on stressful working conditions in Intensive Care Units.